Metabolic Therapy and Pulmonary Disfunction in Patients with Obstetric Sepsis - A. YU. Yakovlev; R. M. Zaitsev; P. S. Zubeev; K. V. Mokrov; A. V. Balandina; N. N. Gushchina; K. E. Kucherenko (Антибиотики и Химиотерапия, 2020)
The role of reamberin, a succinate-containing infusion preparation in correlation of pulmonary metabolic and respiratory disturbances in patients with obstetric puerperal sepsis was estimated. The prospective randomized study enrolled 43 patients with puerperal obstetric sepsis complicated by polyorganic deficiency (SOFA 8-10). Nineteen patients of the 1st group and 24 patients of the 2nd group were additionally treated with reamberin in a dose of 800 ml/day for 8 days. The venous and arterial difference by glucose, lactate, pyruvate, diene conjugates, malondialdehyde and ceruloplasmin was investigated. The blood gases were determined with the Ciba Corning 45 apparatus. Lower metabolic activity of the lungs with prevalence of the glucose anaerobic metabolism and lower activity of the intrapulmonary antioxidant protection were observed in the patients with obstetric sepsis. The use of reamberin in the complex therapy of obstetric sepsis promoted maintenance of the initial balance and anaeroibic and aerobic pulmonary metabolism, thus providing shorter terms of the decompensation and recovery of the lungs respiratory function.